HARNESSING GENERATIVE MODELS FOR MEDICAL IMAGE SYNTHESIS AND AUGMENTATION IN DIAGNOSTIC TASKS - Dr. V. Antony Joe Raja (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
The application of generative models, particularly Generative Adversarial Networks (GANs) and Variational Autoencoders (VAEs), in medical imaging has witnessed rapid evolution. These models hold immense potential for augmenting datasets through synthetic image generation, thereby mitigating issues such as class imbalance and limited data availability. This paper reviews the progress in leveraging generative models for medical image synthesis, focusing on their application in diagnostic imaging tasks. The objective is to understand how synthetic data can enhance deep learning models in terms of performance, generalization, and robustness. It also explores challenges and ethical considerations, offering a structured perspective for future research and clinical integration.